Development of Four-Tier Multiple Choice Test Instrument to Identify Students' Concept Understanding of Newton's Law Material - Fatni Mufit; Syamsidar Syamsidar (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
Physics learning is learning that requires students to understand the concepts. In fact, most students still do not understand the concepts they have learned, especially the concepts in Newton's Law so that it can cause misconceptions. Students' misconceptions on Newton's Law can be identified using diagnostic tests. However, this diagnostic test is not yet available in schools. The purpose of this study was to produce a valid and reliable Four-Tier Multiple Choice Test instrument on Newton’s Laws material. The type of research carried out is design research with the Plomp development model. This research is limited to two steps, which are Preliminary Research and Prototype Phase. The data collection instruments in this study were interview guides, student concept tests, self-evaluation sheets and product validation sheets. The data analysis technique used is descriptive analysis for the interview guides, coding techniques for the concept test, Aiken’s formula for validation sheet and for the reliability using KR-20 formula. The results of preliminary research shows that teachers use more conventional learning which has the potential to cause misconceptions. Meanwhile, more than 50% of students experience misconceptions. Furthermore, the results of the instrument validation are: first, the validity aspect of the instrument scores between 0.56 to 0.79 which are in the valid category. Second, the reliability scores of the instrument is 0,90 which is in the very high category. It means Four-Tier Multiple Choice Test instrument on Newton’s Laws material can be used.